KARATER MAJELIS SEBAGAI PEMIMPIN JEMAAT BERDASARKAN 1 TIMOTIUS 3:8-10 DI GEREJA GPPIK MARANATHA ANTAN RAYAN PONTIANAK KALIMANTAN BARAT: Kata Kunci: Karakter, Majelis, Pemimpin, Jemaat, 1 Timotius 3:8-10 - Nita Ulansari; Sonny Herens Umboh (Sekolah Tinggi Teologi Excelsius, 2024)
Abstract: Leadership in the church plays a crucial role in maintaining the spiritual and social well-being of the congregation. As leaders, the assembly is not only responsible for managing church administration, but also providing spiritual guidance, being a role model, and maintaining harmony among the congregation. From a Biblical perspective, the responsibilities of the assembly are clearly regulated, one of which is in 1 Timothy 3:8-10, which emphasizes the importance of strong character and integrity for the assembly. This verse underscores that the personal qualities of the assembly are an important element in effective leadership in the church. The purpose of this research is to find out what the character of congregation leaders is according to 1 Timothy 3:8-10 at the GPPIK Maranatha Anatan Rayan Pontianak Church, West Kalimantan. The method used is qualitative with a descriptive approach. The results of this research are that a congregation leader must have a good role model attitude, be spiritually mature, and wise to prevent gaps between assemblies and create dynamic and structured management. Leading with honor means maintaining one's attitude, acting wisely, being trustworthy, loyal and honest. A leader must have integrity, not spread gossip, be free from alcohol, and be far from greed that is only selfish. Maintaining faith is also key, where a leader lives holy, is loyal to God, and holds fast to God's word.